Probing Italy: A Scanning Probe Microscopy Storyline - Franco Dinelli; Marco Brucale; Francesco Valle; Cesare Ascoli; Bruno Samorì; Marco Sartore; Manuela Adami; Riccardo Galletti; Stefano Prato; Barbara Troian; Cristiano Albonetti (Micro, 2023)
Starting from the late 1980’s, scanning probe microscopy has progressively diffused in Italy until today. In this paper, we provide a brief account of the main historical events and a current picture of the distribution of the active groups. A survey was prepared by LimeSurvey, made of six sections asking for personal and institutional data, human resources, equipment available, fields of interest, research projects, educational/dissemination activities, and two relevant publications in the last six years. It turns out that the Italian community includes more than seventy groups and two companies. It is widely diffused, although mostly concentrated near large academic and research institutions, often in locations where prominent Italian researchers have operated. This community is active in many scientific fields and can produce research of high international quality. It shows a wide competence, as proven by the list of research works published in journals ranked within the top 20% class. The diffusion of SPM microscopes in industry is still sporadic, possibly due to extensive collaborations between the research institutions and industries themselves. The authors hope that this work might be useful to the community and beyond, and that it might stimulate the formation of a more structured network.